Earth–world–planet: Rural ecologies of horror and dark green criminology - McClanahan, Bill (Theoretical criminology, 2020)
This article responds to green criminology. Drawing on an ethnographic case study of the coal-producing region of Appalachia and the processes of mountaintop removal mining, the article engages contemporary philosophy, ecocriticism, and “dark ecology” to suggest that green criminology rethink its linguistic categories and epistemological assumptions. The article employs an analysis of some examples of horror cinema to suggest criminological engagement with “ecologies of horror” and the “horrors of ecology” that condition life in the shadow of harmful modes of resource extraction. It concludes with some thoughts on the potential of a “dark” green and green-cultural criminology.